Differential Hessian fly (Mayetiola destructor) reactions in resistant and susceptible wheat cultivars - Motolai, Gergely; Chen, Ming-shun (My University, 2017)
Hessian fly is a serious chronic wheat, barley and rye pest, that causes huge economical damage in the US every year. The goal of study was to investigate how the Hessian fly resistant wheat differs from the susceptible wheat after the infestation? Our result showed that the hessian can grow and develop in susceptible wheat, but die in resistant plants. We found differences in protein profiles in host plants when we compare the feeding site vs non-feeding site samples on HPLC. This experiment is important to understand the genetic differences between susceptible and resistant crops and differences in gene expression after the hessian fly injected its saliva. The result of this experiment helps understanding on how the hessian fly manipulates host plants for its benefit.